\[\boxed{\text{328\ (328).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[График\ y = x^{2}\ представим\ в\ \]
\[виде\ y = (x - a)^{2} + b;\]
\[где\ a,\ b - смещение\]
\[вершины\ параболы\ \]
\[(она\ же\ точка\ вершины\ параболы).\]
\[\textbf{а)}\ y = (x - 4)^{2} - 5\]
\[\textbf{б)}\ y = - 2 \cdot (x + 6)^{2} + 7\]
\[\boxed{\text{328.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[y = g(x)\]
\[1)\ f( - 4) = 0,5\]
\[f( - 1) = 2\]
\[f(1) = 2\]
\[f(2,5) = - 0,5\]
\[2)\ f(x) = - 1 \Longrightarrow \ \ \]
\[\Longrightarrow x = - 2\ и\ x = 2\]
\[f(x) = 0 \Longrightarrow \ \ x = - 3;\ \ \]
\[\ x = 1,5;\ \ \ x = 3;\ \ \ x = - 1,5\]
\[f(x) = 2 \Longrightarrow \ \ x = - 1;\ \ \ x = 1\]
\[3)\ E(y) = \lbrack - 1;3\rbrack\text{.\ \ }\]